Geographic patterns and determinants of family planning satisfaction among women of reproductive age in Ethiopia - Natnael Kebede; Rahel Mulatie Anteneh; Natnael Moges; Sintayehu Simie Tsega; Melkamu Aderajew Zemene; Asaye Alamneh Gebeyehu; Melaku Ashagrie Belete; Denekew Tenaw Anley; Ermiyas Alemayehu; Ermias Sisay Chanie; Anteneh Mengist Dessie (Contraception and Reproductive Medicine)
Abstract Introduction While studies in Ethiopia have explored family planning use and contraceptive determinants, limited research examines the spatial variation and predictors of satisfaction with family planning methods. This study addresses this gap using geographically weighted regression (GWR) analysis to assess spatial patterns and determinants of satisfaction with family planning methods among reproductive-age women. Utilizing nationally representative 2021 Performance Monitoring for Action Ethiopia (PMA-ET) data, the study aims to provide targeted insights for improving family planning services. Methods A weighted sample of 1,456 reproductive-age women was analyzed. Spatial analysis was conducted using ArcGIS 10.7 and SaTScan 9.6. Hotspot detection, ordinary least squares (OLS) regression, and geographically weighted regression (GWR) were applied. The Bernoulli model was used to identify spatial clusters of satisfaction. Associations between satisfaction and explanatory variables were assessed using OLS and GWR, with statistical significance set at P < 0.05. Results The overall satisfaction rate with current family planning methods was 84.1% (95% CI: 82.12, 85.97). Satisfaction levels exhibited a clustered spatial distribution. High-satisfaction hotspots were detected in Addis Ababa, most parts of Amhara, and some areas of Benishangul-Gumuz. SaTScan identified a primary spatial cluster (RR = 1.19, P < 0.001) in Addis Ababa, northern southwestern Ethiopia, and eastern Gambela, and a secondary cluster (RR = 1.18, P < 0.001) in northern Addis Ababa and southern Amhara. GWR analysis revealed that younger women (15–24 years), those with poor wealth status, and urban residents were significant spatial predictors of satisfaction. Conclusion The study revealed that satisfaction with the current use of family planning methods among reproductive-age women in Ethiopia exhibits regional variations. Statistically significant clusters of higher satisfaction were identified in Addis Ababa, most parts of Amhara, and some parts of Benishangul-Gumuz. Geographically Weighted Regression (GWR) analysis indicated that women aged 15–24, those with poor wealth status, and urban residents were significant spatial predictors of satisfaction at the local level. These findings suggest the need for targeted regional strategies to improve satisfaction with family planning services. Interventions should prioritize high-satisfaction areas to sustain progress while addressing disparities in underserved regions. Policymakers should focus on enhancing equitable access, strengthening awareness campaigns, and mitigating socioeconomic barriers to improve satisfaction with family planning.